1999
DOI: 10.1159/000051376
|View full text |Cite
|
Sign up to set email alerts
|

Comedolytic Effect of Topical Retinaldehyde in the Rhino Mouse Model

Abstract: Background: Retinaldehyde is a key molecule in the metabolism of vitamin A by keratinocytes. In order to evaluate its range of topical activity in acne, its comedolytic effect was compared to that of retinoic acid in the same vehicle, in the rhino mouse model. Methods: The animals were treated on the back daily for 5 consecutive days per week for 3 weeks. At the end of this period, histological slides were analyzed in order to quantify the features of comedones and epidermal thickness. Results: Topical treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…A 3-week topical treatment induced a significant decrease in both the size and density of dermal cysts, an effect also observed with topical retinoids on the rhino mouse model [12] or the coaltar-induced comedogenesis in the rabbit ear model [Navarro et al, pers. commun.].…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…A 3-week topical treatment induced a significant decrease in both the size and density of dermal cysts, an effect also observed with topical retinoids on the rhino mouse model [12] or the coaltar-induced comedogenesis in the rabbit ear model [Navarro et al, pers. commun.].…”
mentioning
confidence: 85%
“…Likewise, all-trans-retinaldehyde (RAL) is converted by epidermal cells to both storage (all-trans-retinyl esters) and active (RA) forms of vitamin A and exerts significant retinoid biological activities [5][6][7], with a very good local tolerance even at a concentration of 0.1% [10,11]. On the other hand, RAL showed comedolytic [12] and antibacterial activities [13,14]. Recently, ·-hydroxy acids (AHAs) and particularly glycolic acid (GA) gained importance in dermatological applications, such as products against skin ageing.…”
Section: Introductionmentioning
confidence: 99%
“…RAL has revealed a retinoid-like activity in the stimulation of proliferation and differentiation, comedolysis, inhibition of protein expression (in particular melanin) and increase in epidermal thickness [24,26,27]. RAL also shows a specific antibacterial activity against Propionibacterium acnes [28,29].…”
Section: Retinaldehydementioning
confidence: 99%
“…RAL is a key intermediate element in the metabolism of natural vitamin A in human and mouse keratinocytes [8][9][10] and leads to measurable biological activity in the skin [11,12]. Moreover, RAL is well tolerated by humans [12], and, in animal models, RAL works at least as well as retinoic acid in resolving comedonal acne [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, RAL is well tolerated by humans [12], and, in animal models, RAL works at least as well as retinoic acid in resolving comedonal acne [8]. In humans, in vivo and in vitro studies have demonstrated that RAL exerts a direct antibacterial activity against Propionibacterium acnes, while retinoic acid does not [10,13].…”
Section: Introductionmentioning
confidence: 99%